A Marxist Analysis of the Video Game Metal Gear Solid 4: Guns of the Patriots - Sutta Chaiyarasamee (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2019)
This research aimed to investigate from a Marxist perspective in the conflicts between two factions in the video game Metal Gear Solid 4: Guns of the Patriots. In order to study this particular topic, the theory of Karl Marx was used to explain the relationship and conflicts between the two factions appearing in the dialogue script from the game. In addition, Charles Sanders Peirce’s Theory of Signs was used to analyze several footages from the game in order to find evidence of denotation and connotation from a Marxist perspective in the game. According to the analysis of the in-game dialogues, the researcher found several examples that can be analyzed by applying Marxist theory to the game story such as 1) the in-game superior class called “The Patriots,” 2) the inferior groups in the game, and 3) the retaliation of the inferior groups against the superior class. Accordingly, these findings from the dialogues of the game resemble the antagonistic relationship between the oppressing bourgeois class and the exploited proletarian class in Marxist theory. In addition, the semiotic analysis using the Triadic of Signs and three kinds of signs of Charles Sanders Peirce also show significant support from the selected footages for a Marxist theoretical analysis. The footages were found to be indexical and symbolic signs, according to Peirce’s three kinds of signs, which can be explained by applying the concepts of Marxism: 1) the wealth and power of the in-game superior class, 2) the powerlessness and struggles of the inferior groups, and 3) the taking of power by the inferior groups after rebellion and retaliation against the superior class.